Peningkatan Hasil Belajar Matematika tentang Volume Bangun Ruang Menggunakan Model Pembelajaran Student Teams Achievement Division (STAD) - Mahfudloh Mahfudloh (LPPM Institut Agam Islam Nahdlatul Ulama (IAINU) Kebumen, 2021)
This research is a classroom action research conducted in two cycles. Each cycle has 4 steps, namely: Planning, Implementation, Observation and Reflection. The data source for this study was Class V students at MI Islamiyah Brokoh, Wonotunggal District, Batang Regency for the 2019/2020 academic year with a total of 22 students, consisting of 10 male students and 12 female students. Data collection techniques by observation, ability tests and learning outcomes research determine the volume of geometric shapes. The data analysis technique used in this research is qualitative descriptive statistics.Based on the results of the study it can be concluded that the analysis obtained a significant increase from cycle I and cycle II. Study results determine the volume of the geometric shape. in pre-cycle I in the complete category was 59.09% the number of students who completed was 13 students. In cycle II there was an increase in the percentage of student learning outcomes in the complete category of 100%, while 22 students completed.The results of this study suggest for students to be more active so that fun and meaningful learning can be achieved. Suggestions for teachers should use the STAD Type Cooperative approach to improve learning outcomes in determining the volume of geometric shapes. in order to measure the ability of students as a whole